Absurdism and Superstitions: Islamic Perspectives in Albert Camus’s The Plague (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
Many scholars discussing the pandemic issues tend to use Western perspectives. To question this hegemony, this paper investigates Albert Camus’s The Plague (1947) by using Islamic perspectives to challenge the dominant views in evaluating literary canon and pandemic studies. By engaging with postcolonialism and pandemic studies with the frameworks of Islamic studies, this research investigates what differences in pandemic issues are explored in Camus’s novel and how Islam advocates for Muslims to deal with the pandemic problems. The focus of this novel is mainly on European culture and perspectives, although the setting of the novel is Algeria, which is one of the largest Muslim populations in the world. Thus, it is essential to apply the Islamic perspectives in investigating this novel to understand how Islam encourages Muslims to believe and worship God as a way of living instead of being atheists, selfish, and hedonists, as this novel reveals. This research found that the author uses the ideas of absurdism, isolation, and superstitions by depicting the characters as struggling to face the bubonic plague. However, the characters still live in atheism and believe in superstitions instead of worshipping God as Islam advocates.